2014
DOI: 10.1590/s1516-35982014000600001
|View full text |Cite
|
Sign up to set email alerts
|

Biomass accumulation and chemical composition of Massai grass intercropped with forage legumes on an integrated crop-livestock-forest system

Abstract: -The objective was to evaluate the use of woody legumes (Albizia lebbeck, Cratylia argentea, Dipteryx Allata (Baru), a Leucaena hybrid (L. leucocephala + L. diversifolia), and Leucaena leucocephala cv. Cunningham) and herbaceous legumes (Arachis pintoi) intercropped with Panicum maximum cv. Massai, simultaneously implanted in a maize crop. The study made use of a randomized block experimental design with four replications. Assessments of biomass accumulation and forage nutritional value were made after the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…The relative feed value (RFV) of ten varieties of S. guyanensis in a range of 102.8-130.5% [46] [63]. The DMD of Arachis species (AG and AH) was higher (650 and 663 g/kg DM) except LLP than other legume species, which is similar to previous observations [64] where it was reported that the DMD of Arachis species in general is greater than other tropical legumes.…”
Section: Energy Energy Efficiency Intake Digestibility and Relative F...supporting
confidence: 84%
“…The relative feed value (RFV) of ten varieties of S. guyanensis in a range of 102.8-130.5% [46] [63]. The DMD of Arachis species (AG and AH) was higher (650 and 663 g/kg DM) except LLP than other legume species, which is similar to previous observations [64] where it was reported that the DMD of Arachis species in general is greater than other tropical legumes.…”
Section: Energy Energy Efficiency Intake Digestibility and Relative F...supporting
confidence: 84%
“…Em SIPAs tem-se dado maior atenção aos impactos do sistema na produção de biomassa da parte aérea e produtividade de grãos e madeira (FRANCHINI et al, 2014;VOLPE;LEMPP, 2014;TONINI et al, 2016;. No entanto, ainda é incipiente o conhecimento da dinâmica de crescimento do sistema radicular das diferentes espécies cultivadas em sucessão e/ou consórcios nestes sistemas.…”
Section: Introdução Geralunclassified